2017
DOI: 10.1093/jnci/djw279
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib or Erlotinib vs Chemotherapy for EGFR Mutation-Positive Lung Cancer: Individual Patient Data Meta-Analysis of Overall Survival

Abstract: Despite statistically significant PFS benefit, there is no relative OS advantage with frontline gefitinib or erlotinib vs chemotherapy in EGFR -mutated NSCLC. This finding is likely due to the high rate of crossover at progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
190
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(195 citation statements)
references
References 24 publications
3
190
1
1
Order By: Relevance
“…A recent meta-analysis of first line trials of gefitinib or erlotinib vs. chemotherapy showed that 34% of the patients with EGFR TKI did not receive any subsequent treatment after progression. 23 In our study, very few patients switched or got rechallenged on EGFR TKIs, mainly because during that time no EGFR TKIs (osimertinib) were available as a second line treatment option for patients who had developed the T790M resistance mutation after first line treatment. 28 Unfortunately, we did not have access to drugs dispensed to individuals during a hospital stay (e.g., chemotherapy or radiotherapy), creating observation gaps which is likely to have an impact on survival outcome.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent meta-analysis of first line trials of gefitinib or erlotinib vs. chemotherapy showed that 34% of the patients with EGFR TKI did not receive any subsequent treatment after progression. 23 In our study, very few patients switched or got rechallenged on EGFR TKIs, mainly because during that time no EGFR TKIs (osimertinib) were available as a second line treatment option for patients who had developed the T790M resistance mutation after first line treatment. 28 Unfortunately, we did not have access to drugs dispensed to individuals during a hospital stay (e.g., chemotherapy or radiotherapy), creating observation gaps which is likely to have an impact on survival outcome.…”
Section: Discussionmentioning
confidence: 89%
“…The EURTAC trial, 10 enrolled a European patient population with advanced EGFR mutation positive NSCLC, reported OS of 22.9 months for patients treated with Erlotinib first-line treatment. 23 In this trial, the patients had no history of chemotherapy for metastatic disease, median age 65 years, 67% were female and 95% had adenocarcinoma. While patients in our study were older (mean age 67 years), fewer females (59%) and fewer adenocarcinoma (85%).…”
Section: Discussionmentioning
confidence: 94%
“…A meta‐analysis of randomized controlled trials (RCTs) suggested that EGFR‐mutated NSCLC patients treated with first‐line first‐generation EGFR‐TKI (gefitinib or erlotinib) therapy had longer median progression‐free survival (PFS) than chemotherapy‐treated patients (11.0 vs . 5.6 months) . Treatment with the second‐generation EGFR‐TKI afatinib, which irreversibly inhibits EGFR and other ErbB family targets, significantly improved the PFS of untreated EGFR‐mutated patients compared to chemotherapy (11.1 vs .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced disease have lost the opportunity of surgery and thus are treated by chemoradiation or targeted therapy. At present, the most commonly used target drugs for NSCLC treatment are EGFR‐tyrosine kinase inhibitors (TKIs), including gefitinib and erlotinib . However, not all NSCLC patients can benefit from EGFR‐TKI treatment.…”
Section: Introductionmentioning
confidence: 99%